How to Measure Intellectual Capital? (Case Study in Peri Kecil Batik Madura) - Citra Nurhayati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Intellectual capital is the result of the learning process that we do and is invisible or intangible. Although invisible, intellectual capital is the very valuable wealth of an individual. An increasingly dynamic and competitive business environment requires reliable intellectual capital ownership . This study aims to measure intellectual capital consisting of human capital, (1) Human Capital, (2) Structural Capital or Organizational Capital, (3) Relational Capital or Customer Capital. By using qualitative methods, intellectual capital measurement in one of the batik businesses in Bangkalan (Batik Peri Kecil) will be able to find out how much intellectual capital it uses. Keywords: intellectual capital, human capital, structural capital